“Embarazo Ectopico” - Basualdo Ibañez, Marco Antonio (1996)
In a pregnant intrauterine normal, the blastacita is implemented in the endometría which is of uterine cavity. Implantation registered at any other point is designated with the name of ectopic pregnancy. Although more than 95% of pregnant them affect the fallopian tube, tubal pregnancy is not synonymous with ectopic gestation, ~ ino just Pl latest Chick of this mode. We also have that it is more common in black women than in white women and is considered also the situation sacioeconomica, inadequate sexual habits as promiscuity, resurgence of sexually transmitted diseases, patients in treatment of infertility.